Development and application of mass open online Lean production classes in the pandemic conditions - Vitaly Anatolyevich Dovgal; Galina Vladimirovna Karamushko; Natalia Gennadievna Maskova; Sergey Georgievich Chefranov (Вестник Майкопского государственного технологического университета, 2023)
The objective process of expanding application of digital technologies, significantly accelerated and enhanced by the pandemic, has identified a number of promising directions in training both within the framework of university educational programs and in the postgraduate development system of competences. Among adequate education formats the so-called MOOCs are allocated - mass open online courses, which have become particularly popular in the conditions of insulation of people caused by the coronavirus pandemic. The problem: reformatting educational material in order to transfer it to a remote type with the use of educational technologies of e-learning - interactive elements, various media formats, etc. The purpose of the research is to show the possibility of transferring online management personnel to the skills of the application of the principles and instruments of Lean production based on the developed mass open course in order to master the lean technologies, if necessary, the translation of the educational process into electronic form in the pandemic period. The research methods used are critical analysis of pedagogical, psychological and regulatory sources, design, modeling, systematization. The research results are the following: the article shows the practical possibility of digital transformation of the learning process and lean production tools in a remote form on the basis of mass open online courses conducted in the pandemic period with the help of an electronic information educational environment of the University. The tasks of the online course and its structure are also given, experience has been described with training groups of employees of manufacturing divisions and administrative workers, whose heterogeneity requires special attention, the process and peculiarities of transfer of lean production teaching to the online format have been described. Key findings: training in the online format allows to improve special knowledge in a convenient form, to acquaint employees with corporate values and strengthen the competitive advantages of an organization by forming an excellently prepared team, armed with lean production skills.